Electrocatalysts for photochemical water-splitting - Kalanur, Shankara S.; Seo, Hyungtak (Methods for Electrocatalysis: Advanced Materials and Allied Applications, 2020)
The photochemical water splitting to produce O2 and H2 is considered as the most promising, sustainable, renewable and cost-effective energy technology for the future. In photochemical water splitting process, the efficiency of H2 and O2 production rates depends on the properties of the selected semiconductor material. However, most of the semiconductors face various limitations which confines their water splitting efficiency. Different strategies could be implemented to improve the water splitting efficiency of semiconductors. Among them, loading of catalyst onto the water splittingmaterial is known to be one of the effective strategy to enhance the H2 andO2 production rates.Given this, several catalytic materials have been explored and successfully utilized in efficient O2 and H2 production systems. In this chapter, we summarize some of the effective O2 and H2 production catalysts derived from noblemetal, noblemetal oxides, earth-abundant metals and oxides, metal phosphides and metal chalcogenides. The surface deposited catalysts were known to reduce the surface trap states, which decreases the charge recombination and acts as protective layer to minimize photo-corrosion of the light absorbing semiconductors. Conclusively, to explore the efficient catalysts for photochemicalwater splitting require more research contribution towards the understanding of the core reaction mechanism of catalytic process with the use of sustainable and stable materials.
Keywords: Catalysts; Gas production; Metal oxides; Noble metals; Photochemical water splitting